Gender, Caste, and Colonialism: The Historical Construction of Indian Womanhood - Pandian, Lydia VK (Journal of Gender and Power, 2024)
Studying colonial translations of upper-caste Brahminical texts to contextualize ancient Indian women’s status, began in the 19th and early 20th centuries and was influenced by Western positivist perspectives. Despite the diversity of thought found in the ancient texts and historical contexts, positivistic interpretations continue to play a significant role in perpetuating stereotypes, confining women to narrow roles within patriarchal and colonial frameworks. In contrast to these prevailing narratives, pre-Vedic Indian society demonstrated egalitarian dispositions, with women actively engaged in various socioeconomic spheres of life. Colonial historiography’s oversimplification of ancient Indian women’s experiences failed to account for regional, linguistic, and cultural distinctions, obscuring the intricate realities of their lives. By threading these historical dynamics into our analysis, we gain insight into the rich tapestry of their experiences and contributions within the shadows of patriarchal and colonial ideologies.